The effects of the London 2012 Olympics and related urban regeneration on physical and mental health: the ORiEL mixed-methods evaluation of a natural experiment - Cummins, S; Clark, C; Lewis, D; Smith, N; Thompson, C; Smuk, M; Stansfeld, S; Taylor, S; Fahy, A; Greenhalgh, T; Eldridge, S (NIHR Journals Library, 2018)
Background There is limited evidence for public health policy-makers on the health impacts of urban regeneration programmes.